PEMBINAAN KEAGAMAAN MASYARAKAT KOTA BANDUNG MELALUI PROGRAM MAGRIB MENGAJI: STUDI KASUS PADA MASJID AL-FITHROH KECAMATAN BANDUNG KULON - Sugestian, Gansah; Syafei, Makhmud; Fakhruddin, Agus (TARBAWY : Indonesian Journal of Islamic Education, 2017)
Education is not only roled by a school but also the education become a responsible for all of stake holder such as school, family, and government called TRISENTA (three centers of education). Ultimately, the government has responsible to develop education through creating policies. This study explained the policy of Bandungâ€™s mayor about studying islamic maghreb program which will be evaluated the enforces of the policy in society. Therefore, I create a research about â€œDevelopment of Religion on Bandungâ€™s Society by Studying Islamic Maghreb Programâ€ (case study at Al-Fithroh mosque in Bandung Kulon). The purpose of this study is to observe an comprehension of head of the Al-Fithroh mosque regarding studying islamic maghreb program, human resource, enforcement procedure of studying islamic maghreb program, and the goal achievement of studying islamic maghreb program. The method of this study is descriptive with qualitative approach. Interview, observation, and documentation study are the technique to collect a data in this study. The results are : 1) the comprehension of Al-Fithrohâ€™s head has corresponded with what the goals of studying islamic maghreb program are ; 2) Al-Fithroh has one teacher and good facilities supported by donors and cash ; 3) procedure enforcement divide to three steps; first, student learn to recognize the words of Qurâ€™an ; second, student is demanded to memorize short surah (juzâ€™ama); third, the students have to understand the meaning of Qurâ€™an. 4) Al-Fithroh has good achievement in implementing studying islamic maghreb program. Moreover, the teacher not only teach the religion subject but also give a soft skill as additional program.Â Penelitian ini berkenaan dengan kebijakan Wali Kota Bandung tentang program Magrib Mengaji, untuk mengetahui bagaimana implementasi program tersebut. Tujuan penelitian ini adalah mengetahui pemahaman DKM Al-Fithroh terhadap program Magrib Mengaji, sumber daya yang dimiliki, prosedur pelaksanaan program Magrib Mengaji, dan ketercapaian program Magrib Mengaji di masjid Al-Fithroh. Demi mendapatkan data yang sesuai, penelitian ini menggunakan metode deskriptif analisis dengan pendekatan kualitatif. Hasil penelitian ini meliputi: 1) pemahaman DKM Al-Fithroh tentang program Magrib Mengaji telah sesuai dengan tujuan program Magrib Mengaji; 2) Sumber daya dan sarana prasarana yang dimiliki masjid Al-Fithroh sangat menunjang; 3) Prosedur pelaksanaan program Magrib Mengaji yang terdiri dari tiga tahap; 4) Ketercapaian program Magrib Mengaji yang yang telah dicapai DKM Al-Fithroh sudah tercapai dengan optimal dan lebih dari itu karena ada program soft skills yang membuat anak-anak selain dibekali ilmu agama namun dibekali juga skill yang dapat mereka pergunakan di kemudian hari.Â Kata Kunci: Baca-Tulis Alquran, Kebijakan, Pembelajaran, Program Magrib Mengaji.